2005
DOI: 10.1212/01.wnl.0000148586.79290.a6
|View full text |Cite
|
Sign up to set email alerts
|

Grief support for informal caregivers of patients with ALS: A national survey

Abstract: Providing emotional support to caregivers is integral to comprehensive ALS care. The authors surveyed ALS Association centers and clinics and Muscular Dystrophy Association/ALS centers. Respondents thought that grief and bereavement support was integral to ALS care but thought that the support provided by their centers was often inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Although the VFS is commonly used for a general evaluation of dysphagia [13], quantitative analysis is difficult. The new devices for assessing MTP and IPG provided additional data for quantitative analysis (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the VFS is commonly used for a general evaluation of dysphagia [13], quantitative analysis is difficult. The new devices for assessing MTP and IPG provided additional data for quantitative analysis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1A). The videofluoroscopic swallow study (VFS) is a classic technique that evaluates all four stages of the swallowing process [13]. In contrast, new digital apparatus for assessing maximal tongue pressure (MTP) can selectively evaluate the oral stage [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Pagnini (37) Australian study demonstrated that MND family caregivers are at risk of prolonged grief (42). While there is a strong recognition for the value of grief and bereavement support, this support is often inadequate (41,42). In a 2001 Canadian study, 37% of caregivers were coping poorly or very poorly, sometimes years after death (28).…”
Section: End-of-life Caregiving and Requests For Hastened Deathmentioning
confidence: 99%
“…The most commonly documented mental and psychological health symptoms and issues among MND caregivers included depression (13, 15, 39-41, 45, 46, 60, 63, 64); psychological distress (15,40,50,57,60); and anxiety (27,41,46,57,62,63,65).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…33,34 Several authors have recommended that involvement in palliative care services for people with NDDs should occur relatively early in the course of the illness, anticipating active caregivers' needs well in advance of predictable physical deterioration, and assisting with later stage symptoms, psychosocial issues and decision making about the levels of active clinical intervention. 35,36 NDD caregivers reported that those who received more tailored services and SPCS input were the most satisfied, highlighting the need for responsive and flexible models of care for people with NDD and their caregivers.…”
Section: Aoun Et Almentioning
confidence: 99%